Efektivitas Pendekatan Kontekstual dalam Pembelajaran Menulis Teks Negosiasi - Yani Siti Asyani (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2017)
This article discusses the effectiveness of a contextual approach to learning writing negotiating texts. The research was conducted to find out the influence and the result of learning to write negotiation text with contextual approach. The research method used is quasi experiment with One group Pretest-Posttest Design. The selected population is class X SMK Negeri 1 Bojongpicung with a sample of students of class X ATPH 1 amounted to 28 people. Data were collected using test, questionnaire, and observation techniques with test sheet, questionnaire, and observation. The results of the observation sheet indicate the active learners learn when using a contextual approach. From the test results, it is known that the average value of the initial test is 66.89 while the mean score of the final test is 87.64. After comparing the mean of the two test results, calculations were performed using the t-Test. The calculation result with t-test shows the tcount price is bigger than ttable price. The tcount price is 17.00, while the ttable price at db 27 for the 0.05 level of trust is 2.05. Thus the proposed hypothesis can be accepted, ie the existence of a significant influence in the use of contextual approaches to the results of learning to write negotiation text. This shows the learning of writing negotiated text by applying a better contextual approach than without applying a contextual approach. Keywords: effectiveness, contextual, negotiation.